Risk factors of premature rupture of membranes in public hospitals at Mekele city, Tigray, a case control study - Natnael Etsay Assefa; Hailemariam Berhe; Fiseha Girma; Kidanemariam Berhe; Yodit Zewdie Berhe; Gdiom Gebreheat; Weldu Mamu Werid; Almaz Berhe; Hagos B Rufae; Guesh Welu (BMC, 2018)
Abstract Background The incidence of premature rupture of membranes ranges from about 5% to 10% of all deliveries. A woman with premature rupture of membranes is at risk of intra-amniotic infection, postpartum infection, endometritis, and death. A neonate born from premature rupture of membranes mother is at high risk of respiratory distress syndrome, sepsis, intraventricular hemorrhage and death. Little is known regarding the risk factors in Ethiopia. Therefore, this study was conducted to identify risk factors of premature rupture of membranes among pregnant women admitted to public hospitals in Mekelle city, Tigray, Ethiopia. Methods Hospital based unmatched case control study design was implemented on 240 samples (160 controls and 80 cases) from pregnant mothers admitted to public hospitals in Mekelle city from February - April/2016. Data was collected by interviewer administered Structured questionnaire and checklist. Binary logistic regression model was used to see the association between dependent and independent variables and multivariable logistic regression was used to identify the independent predictors of premature rupture of membranes. Results A total of 160 controls and 80 cases were enrolled in the study. Multivariable logistic regression showed that history of abortion [AOR 3.06 (CI: 1.39, 6.71)], history of PROM [AOR 4.45 (CI: 1.87, 10.6)], history of caesarean section [AOR 3.15(CI: 1.05, 9.46)] and abnormal vaginal discharge in the index pregnancy [AOR 3.31(CI: 1.67, 6.56)] were positively associated with premature rupture of membranes. Conclusions Past obstetric history and risks in the index pregnancy have an association with premature rupture of membranes. The finding of the study suggests early identification and treatment of genitourinary infection.